HARMONY OF HUSBAND-WIFE RELATION IN ISLAMIC RELIGION: MUBADALAH AND ATTACHMENT THEORY INTEGRATIVE ANALYSIS ON AL-BAQARAH 223 - Auliyah, Iqna; Kusnadi; Apriyanti; Ghozi Mubarok; Mohammad Fatah (UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to analyze in depth the harmony in husband and wife relations as implied in Surah al-Baqarah verse 223. This study integrates two relevant theoretical frameworks, namely the Mubadalah theory and Attachment theory. The Mubadalah theory, with its focus on reciprocal and mutual relations, is used to examine the implications of the verse on the dynamics of equal and mutually beneficial interactions in marriage. Meanwhile, the Attachment theory, which emphasizes emotional bonds and the need for security in relationships, is applied to understand how the verse contributes to the formation and maintenance of intimacy and emotional support between husband and wife. This study uses a qualitative approach that is library research. In interpreting the verse, this study uses the tahlili method. The primary data sources in this study are several classical and contemporary tafsir books, the mubadalah theory book by Faqihuddin Abdul Kodir and the attachment theory psychology book by John Bowlby. The secondary data in this study are: articles, journals, dissertations, family relationship books, and scientific papers which are relevant to the discussion of this study. The results of the study show that the integrative analysis of the mubadalah theory towards QS. Surah al-Baqarah verse 223; the wife has the same rights in the household, both in intimate relationships, love, rights and obligations as well as in decision making. Meanwhile, the integrative analysis of the Attachment theory with QS. Surah al-Baqarah verse 223 implicitly shows that the husband is the caregiver for his wife and the wife is the caregiver for her husband. The sacred agreement in marriage requires both the wife and husband to be present not only physically but also emotionally so that both become a safe place in the household. Keywords: Harmony, Al-Baqarah 223, Mubadalah, Attachment Penelitian ini bertujuan untuk menganalisis secara mendalam harmoni dalam relasi suami istri sebagaimana tersirat dalam Surah al-Baqarah ayat 223. Penelitian ini mengintegrasikan dua kerangka teoritis yang relevan, yaitu teori Mubadalah dan teori Attachment. Teori Mubadalah, dengan fokusnya pada relasi timbal balik dan kesalingan, digunakan untuk mengkaji implikasi ayat terhadap dinamika interaksi yang setara dan saling menguntungkan dalam perkawinan. Sementara itu, teori Attachment, yang menekankan pada ikatan emosional dan kebutuhan akan rasa aman dalam hubungan, diterapkan untuk memahami bagaimana ayat tersebut berkontribusi pada pembentukan dan pemeliharaan keintiman serta dukungan emosional antara suami dan istri. Penelitian ini menggunakan pendekatan kualitatif yang bersifat kepustakaan (Library Research). Dalam menafsirkan ayat, penelitian ini menggunakan metode tahlili. Sumber data primer dalam penelitian ini yaitu beberapa kitab tafsir klasik dan kontemporer, buku teori mubadalah karya Faqihuddin Abdul Kodir dan buku psikologi attachment theory karya John Bowlby. Adapun data sekunder dalam penelitian ini yaitu: artikel, jurnal, disertasi, buku relasi keluarga, dan karya tulis ilmiah yang mana relevan dengan pemembahasan penelitian ini. Hasil penelitian menunjukkan bahwa analisis integratif teori mubadalah terhadap QS. Surah al-Baqarah ayat 223; istri memiliki hak yang sama dalam rumah tangga, baik dalam hubungan intim, cinta kasih, hak dan kewajiban serta dalam pengambilan keputusan. Sedangkan Analisis integratif teori Attachment dengan QS. Surah al-Baqarah ayat 223 secara implisit menunjukkan bahwa suami adalah pengasuh bagi istrinya dan istri adalah pengasuh bagi suaminya. Perjanjian sakral dalam pernikahan menuntut pasangan baik istri/suami tidak hanya hadir secara fisik tapi juga hadir secara emosional sehingga keduanya sam-sama menjadi tempat aman dalam rumah tangga. Kata Kunci: Harmoni, Al-Baqarah 223, Mubadalah, Attachment